COVID-19 Emergency and Post-Emergency in Italian Cancer Patients: How Can Patients Be Assisted? - Crispo, Anna; Montagnese, Concetta; Perri, Francesco; Grimaldi, Maria; Bimonte, Sabrina; Augustin, Livia Silvia; Amore, Alfonso; Celentano, Egidio; Di Napoli, Marilena; Cascella, Marco; Pignata, Sandro (Frontiers in Oncology, 2020)
Italy and worldwide are experiencing an outbreak of a new coronavirus-related disease, named COVID-19, declared by the WHO COVID-19 a pandemic. The fragility of cancer patients is well-known, with many cases affecting aged patients or those with several comorbidities that frequently result in a loss of independency and functionality. Therefore, cancer patients have been greatly affected by this health emergency and, due to their vulnerability to COVID-19, oncologic patient visits have been often delayed or cancelled leading to possible undertreatment. Different solutions can be adopted for reducing travels to cancer screening centers and the overall impact of cancer screening visits. As a consequence, it has been recommended that, when possible, the follow-up visits for cancer patients treated with oral anticancer drugs could be performed telematically. Furthermore, many patients refuse hospital visits, even if necessary, because of fear of contagion. Moreover, in some regions in Italy even the very first non-urgent visits have been postponed with the consequent delay in diagnosis, which may negatively affect disease prognosis. For these reasons, new approaches are needed such as the telemedicine tool. Throughout organized and appropriate tools, it would be possible to manage patients’ visits and treatments, to avoid the dangerous extension of waiting lists when the standard activities will resume. In this context, a number of hospital visits can be substituted with visits at small local health centres, and general practitioners’office, taking in turn, advantage of well-defined telemedicine path which will be developed in the post-emergency phase.